2009
DOI: 10.1080/15388220903341372
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization Among Urban, Predominantly African American Youth: Coping With Relational Aggression Between Friends

Abstract: Although there is a growing body of research documenting the deleterious effect of experiencing relational aggression, few studies have explored how children cope with relational aggression, especially when it occurs between close friends. Moreover, relational aggression is understudied among urban African American children. Using data from a sample of 126 urban, low-income predominantly African American children we examined children's beliefs concerning relational aggression and their use of coping strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…Despite some initial work on SES and relational victimization, more studies are needed to clarify and reconcile the inconsistent literature. In addition, to support the generalizability of our findings and to understand how processes may differ among children and adolescents from various backgrounds, future studies are needed with ethnically diverse samples (e.g., Kliewer, Dibble, Goodman, & Sullivan, 2012;Waasdorp, Bagdi, & Bradshaw, 2010) and among sexual minority youth (e.g., Williams, Connolly, Pepler, & Craig, 2005).…”
Section: Crucial Future Directions and Recommendationsmentioning
confidence: 99%
“…Despite some initial work on SES and relational victimization, more studies are needed to clarify and reconcile the inconsistent literature. In addition, to support the generalizability of our findings and to understand how processes may differ among children and adolescents from various backgrounds, future studies are needed with ethnically diverse samples (e.g., Kliewer, Dibble, Goodman, & Sullivan, 2012;Waasdorp, Bagdi, & Bradshaw, 2010) and among sexual minority youth (e.g., Williams, Connolly, Pepler, & Craig, 2005).…”
Section: Crucial Future Directions and Recommendationsmentioning
confidence: 99%
“…Three items assessed the children's beliefs about relational aggression (Waasdorp et al 2009). The items assessed whether they perceived that many children experience relational aggression within close friendships (0 = no, 1 = yes); their perception of the frequency with which relational aggression occurs within children's friendships (1 = rarely, 2 = sometimes, 3 = often); and the perceived sex of the children who are more likely to experience relational aggression within friendships (1 = mostly girls, 2 = mostly boys, 3 = both boys and girls).…”
Section: Methodsmentioning
confidence: 99%
“…Children responded to a series of questions about the sex and age of their close friends, their satisfaction with their friendships, and whether they experienced relational aggression within their friendships (see Table 1) (Waasdorp et al 2009). We constructed a series of parallel items for parents, in which they reported their perceptions of their child's friendships and experiences with relational aggression.…”
Section: Methodsmentioning
confidence: 99%
“…Leff et al (2009) stated that there is a "greater risk for emotional, academic, and behavioral problems for youth living in inner-city settings" (p. 262). Waasdorp, Bagdi & Bradshaw (2009) Sandstrom, 2004). Results indicated that both boys and girls perceived RA to be prevalent and harmful, and that the most frequent coping strategy that they used was ruminative/avoidance (keeping thinking about the RA they received from a close friend).…”
Section: Development Of Relational Aggressionmentioning
confidence: 89%
“…Examples of self-report instruments include the Indirect, Social and Relational Aggression Scale (ISRA), which measures perceived harmfulness of RA (Waasdorp et al, 2009) and the English Version of the Relational Aggression and Victimization Scale (RAVS; Lagerspetz, Bjorkqvist, & Peltonen, 1988as cited in Craig, 1998. Cronbach alphas for the ISRA were .93 for Part I and .94 for Part II.…”
Section: Measuring Relational Aggressionmentioning
confidence: 99%